Picture Perfect? The Role of Instagram in Issue Agenda Setting During the 2016 Presidential Primary Campaign. (August 2018) - Towner, Terri L.; Muñoz, Caroline Lego
Instagram emerged as a pivotal campaign tool in the 2016 presidential campaign. This study examines the agenda-setting effects between the presidential primary candidates' Instagram posts and articles published in the mainstream newspapers during the primary period. A reciprocal relationship between Democratic and Republican candidates' Instagram posts and newspaper articles is expected. A content analysis of issues recorded daily issue frequencies in each medium which were then examined using a time-series analysis. Results offer evidence of a relationship between Democratic and Republican candidates' Instagram posts and newspapers on some of the top issues in the primary campaign. However, the findings also reveal that candidate Instagram posts independently predicted newspapers' issue agendas on certain issues with no reverse effects.